Impact of synthetic routes on the structural and physical properties of butyl-1, 4-diammonium lead iodide semiconductors. Issue 23 (8th February 2017) - Safdari, Majid; Phuyal, Dibya; Philippe, Bertrand; Svensson, Per H.; Butorin, Sergei M.; Kvashnina, Kristina O.; Rensmo, Håkan; Kloo, Lars; Gardner, James M.
Abstract : We report the significant role of synthetic routes and the importance of solvents in the synthesis of organic–inorganic lead iodide materials. Abstract : We report the significant role of synthetic routes and the importance of solvents in the synthesis of organic–inorganic lead iodide materials. Through one route, the intercalation of dimethylformamide in the crystal structure was observed leading to a one–dimensional (1D) [NH3 (CH2 )4 NH3 ]Pb2 I6 structure of the product. This product was compared with the two-dimensional (2D) [NH3 (CH2 )4 NH3 ]PbI4 recovered from aqueous solvent based synthesis with the same precursors. UV-visible absorption spectroscopy showed a red-shift of 0.1 eV for the band gap of the 1D network in relation to the 2D system. This shift primarily originates from a shift in the valence band edge as determined from photoelectron- and X-ray spectroscopy results. These findings also suggest the iodide 5p orbital as the principal component in the density of states in the valence band edge. Single crystal data show a change in the local coordination around iodide, while in both materials, lead atoms are surrounded by iodide atoms in octahedral units. The conductivity of the one-dimensional material ([NH3 (CH2 )4 NH3 ]Pb2 I6 ) was 50% of the two-dimensional material ([NH3 (CH2 )4 NH3 ]PbI4 ). The fabricated solar cells reflect these changes in the chemical and electronic structure of both materials, although the total light conversion efficiencies of solar cells based on both products were similar.